Velocity based artificial bee colony algorithm for high dimensional continuous optimization problems - Imanian, Nafiseh; Shiri, Mohammad Ebrahim; Moradi, Parham (Engineering applications of artificial intelligence, 2014)
Artificial bee colony (ABC) is a swarm optimization algorithm which has been shown to be more effective than the other population based algorithms such as genetic algorithm (GA), particle swarm optimization (PSO) and ant colony optimization (ACO). Since it was invented, it has received significant interest from researchers studying in different fields because of having fewer control parameters, high global search ability and ease of implementation. Although ABC is good at exploration, the main drawback is its poor exploitation which results in an issue on convergence speed in some cases. Inspired by particle swarm optimization, we propose a modified ABC algorithm called VABC, to overcome this insufficiency by applying a new search equation in the onlooker phase, which uses the PSO search strategy to guide the search for candidate solutions. The experimental results tested on numerical benchmark functions show that the VABC has good performance compared with PSO and ABC. Moreover, the performance of the proposed algorithm is also compared with those of state-of-the-art hybrid methods and the results demonstrate that the proposed method has a higher convergence speed and better search ability for almost all functions. •We propose a hybrid ABC algorithm so called VABC for numerical function optimization.•Inspiring from the PSO, the VABC improves the ABC׳s exploitation strategy.•The VABC considers a velocity value for each particle in the onlooker search equation.•The VABC is compared with ABC, PSO and the seven state-of-the-art hybrid methods.•The results show that the VABC has higher convergence speed and better search ability.